(untitled) (Revista de Ciências Agroveterinárias, 2025)
Intangible assets play a crucial role in fostering innovation and enhancing productivity across various industries, particularly due to their capacity to generate competitive advantages. In the agricultural sector, despite their slow adoption, these assets have a significant impact in the context of global challenges and the increasing need for sustainable practices. This systematic review investigates how the contribution of intangible assets to innovation has been studied in the agricultural sector. Using the PRISMA methodology, articles from the Scopus and Web of Science databases published between 1992 and 2024 were reviewed, identifying 46 studies that examine the relationship between intangible assets and innovation in this field. The findings reveal a growing interest in this area, underscoring the pivotal role of intangible assets in improving efficiency and competitiveness in the agricultural sector through innovation. Nonetheless, the review highlights the need for an integrative framework to provide a holistic understanding of how agricultural practices can be enhanced through the effective management of intangible assets.